Getting Higher Critical Thinking Skills through Analyzing and Responding to Text - Besral, Besral (English Education: Jurnal Tadris Bahasa Inggris, 2022)
Understanding the academic text in English requires the ability to think critically and respond to it precisely by way of writings.  This reserach is aimed at improving the students’ critical reading ability through the use of Double Entry Journal. To achieve such competences, we have conducted a Classroom Action Research by involving a group of at risk studentsh who were struggling to complete the course of Reading at 5th  semester.  Throughout 2 cycles, we found out that students’ critical thinking did not only get improved in their reading activity, but also in their oral performances.  Data shows that students’ oral performance was better in fiction work. In addition to the use of DEJ, the article further discusses types of students’ activity that might achieve critical thinking skills particularly in the development of their reading, speaking, and writing skills.Key words: Major Types of Non-Fiction